Moderating Resistances: The Reproduction of Muslim Religious Space in the Dutch East Indies - Faizi, Fuad (Al-Jami'ah: Journal of Islamic Studies, 2023)
This study seeks to historically elaborate on the roots of moderate Islam, focusing on the productive practices towards religious spaces in the Dutch colonial periods in the East Indies. It analyses the strategic changes in the Dutch reproduction of religious space during the Aceh War and the Sarekat Islam periods. The author argues that the Dutch government frequently seized Muslim religious space to secure its colonial power. The colonial government reproduced Muslim religious space in these two eras, representing symbolic support for the Dutch colonial hegemony. The appropriation of religious space was a spatial strategy to perpetuate the hegemony in social space. This study concludes that the reproduction of Muslim space represented a moderate position towards the Dutch colonial hegemony. Meanwhile, counter-space emerged to reverse such moderating practices. By counter-space, the Dutch moderating efforts on socio-religious space were contested, opposed, and condemned.[Kajian ini berupaya menguraikan secara historis akar Islam moderat, dengan fokus pada praktik produksi ruang keagamaan pada masa penjajahan Belanda di Indonesia. Analisis difokuskan pada perubahan strategi pemerintah kolonial Belanda dalam melakukan reproduksi ruang keagamaan selama periode Perang Aceh dan Sarekat Islam. Pemerintah Belanda sering merebut ruang keagamaan umat Islam untuk mengamankan kekuasaannya. Pemerintah kolonial mereproduksi ruang keagamaan umat Islam pada dua era tersebut sebagai merupakan simbol dukungan terhadap hegemoni kolonial Belanda. Perampasan ruang keagamaan merupakan strategi spasial untuk melanggengkan hegemoni atas ruang sosial. Kajian ini menyimpulkan bahwa reproduksi ruang keagamaan Islam merepresentasikan posisi moderat terhadap hegemoni kolonial. Sementara itu, ruang perlawanan muncul untuk membalikkan praktik-praktik moderasi tersebut. Melalui ruang perlawanan ini, upaya-upaya moderasi pemerintah kolonial Belanda dalam bidang sosial-keagamaan ditentang, ditantang, dan dikecam.]